2000
DOI: 10.1159/000028936
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyxoma of the Petrous Apex

Abstract: The common petroclival bony tumors are chordoma and chondrosarcoma. Myxoma of the bone occurs only in the facial bones, and it has not been reported in skull bones. The computed tomographic scanning, magnetic resonance imaging and intraoperative characteristics of a case of fibromyxoma of the petrous bone in a 14-year-old girl are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…With respect to RT, Guha-Thakurta et al 8 noted that it is used only to reduce the size of large tumors and that preoperative embolization can be used to decrease the vascularity during resection. Sato et al, 32 Osterdock et al, 24 and Srinivasan 34 have reported that myxoid tumors are generally insensitive to RT and that postoperative RT has no therapeutic effect on myxomas of the bone in other areas; therefore, RT after surgery is unnecessary. However, Zhang et al 40 reported that among 8 cases receiving postoperative RT, 4 cases did not recur within the followup period.…”
Section: Progression-free Survival and Risk Factorsmentioning
confidence: 99%
“…With respect to RT, Guha-Thakurta et al 8 noted that it is used only to reduce the size of large tumors and that preoperative embolization can be used to decrease the vascularity during resection. Sato et al, 32 Osterdock et al, 24 and Srinivasan 34 have reported that myxoid tumors are generally insensitive to RT and that postoperative RT has no therapeutic effect on myxomas of the bone in other areas; therefore, RT after surgery is unnecessary. However, Zhang et al 40 reported that among 8 cases receiving postoperative RT, 4 cases did not recur within the followup period.…”
Section: Progression-free Survival and Risk Factorsmentioning
confidence: 99%
“…A comparable histopathology was identified in three other cases 12–14 (Table I). Histopathologic identification of proliferating fibroblasts‐fibrous tissue bands in the stroma, 15 fibromyxoid components, vascular spaces, cystic areas, focal fibrous and bony tissue, 16 atypical cellular elements, lipoblasts and mineralization, 17 abundant vascularity 18 or mitotic activity, bone areas with osteoblastic activity, and cysts as sign of degeneration 11 excluded these cases from the group of true primary myxomas. Moreover, one case clearly revealed a myxoma that was finally identified to be a metastasis from an atrial myxoma 19 .…”
Section: Resultsmentioning
confidence: 99%
“…Currently, for the head and neck region, myxomas are considered as a lesion that may derive from tooth germ cells, originating from the dental papilla, because of its predilection for the jaws in young adults, the presence of remnant odontogenic tissue within the tumor, and the association with unerupted teeth (i.e., odontogenic myxoma) 20 . Others believe that myxomas arise from primitive embryonic mesenchyme or fibroblasts with abundant proliferation of mucopolysaccharides because of its resemblance to the primitive connective tissue of the embryo 8,15,21 . The theory that it may arise from myxoblast cells or is a modified form of fibroma is not yet commonly accepted 22 .…”
Section: Discussionmentioning
confidence: 99%
“…2 Fibromyxoma of petrous apex has also been reported. 3,4 This case is described to highlight the clinical presentation and management of this relatively rare neoplasm.…”
Section: Introductionmentioning
confidence: 98%